정서적 성향 및 상사부하 교환관계가 직무긴장, 조직시민 행동에 미치는 영향 - 배성현(Bae, Seung-Hyun); 최은희(Choi, Eun-Hee) (대한경영학회지, 2007)
1980년대 중반 이후 기존에 많이 연구되던 성격유형과는 달리 크게 주목 받고 있는 새로운 성격유형이 정서적 성향 즉 긍정적 성향과 부정적 성향이다. 또한 사회적 교환이론을 근거로 한 상사부하 교환관계(LMX)도 구성원의 태도와 행동 그리고 조직성과에 영향을 준다는 연구가 많다. 본 연구는 정서적 성향(긍정적 성향과 부정적 성향) 및 상사부하 교환관계가 직무긴장과 조직시민행동과(OCB)의 관계를 연구하였다. 그리고 이들의 관계에서 지각된 조직지원의 조절역할을 검증하였다. 조사 대상은 대형 병원 종업원 298명을 대상으로 하였다. 본 연구의 결과 직무긴장에는 부정적 성향은 중요한 설명변수이고 정의 관계를 보여주었으나 긍정적 성향은 유의한 설명변수가 되지 못했다. 반대로 조직시민행동에는 부정적 성향은 관계가 없었으나 긍정적 성향은 높은 정의 관계를 보여주었다. 이 같은 결과는 최근 많은 연구가 이루어지고 있는 정서적 성향(긍정적 성향/ 부정적 성향)이 구성원의 태도와 행동 그리고 조직성과에 중요한 역할을 할 수 있음을 의미한다. LMX도 직무긴장 및 OCB에 유의한 설명변수이었다. 높은 질의 LMX에서는 구성원의 직무긴장을 감소시키고 OCB를 증가시킬 수 있음을 알 수 있다. 정서적 성향, 상사부하 교환관계와 직무긴장 및 조직시민행동과의 관계에서 지각된 조직지원의 조절효과를 분석한 결과, 지각된 조직지원이 직무긴장을 조절하지는 않았으나 조직시민행동에는 조절효과가 상당부분 나타났다. 이러한 결과의 의미는 조직시민행동 관리를 위해서는 상사부하 교환관계와 지각된 조직지원이 함께 관리되는 것이 중요하다는 의미다. 본 연구 결과의 의미는 조직구성원의 성격유형이 긍정적 성향은 높을수록, 부정적 성향은 낮을수록 조직에 공헌할 수 있다는 것이다. 이러한 결과는 조직행동 연구의 이론적 차원뿐만 아니라 실무적 차원에서 채용과 선발, 직무배치전환, 인사고과 등 다양한 부분에 적용될 수 있다. Affective disposition, as a new personality type distinguished from those widely studied before, has been studied since the mid-1980s, as categorized into positive affectivity(PA) and negative affectivity(NA). Leader-member exchange (LMX), based on the theory of social exchange, as an influence on the employee's attitude, behavior, and organizational performance, has also been studied from various approaches. This study examines the relationship between affective disposition (positive affectivity and negative affectivity) and LMX and job strain and organizational citizenship behavior(OCB). The moderating effects of the perceived organizational support(POS) in the relationship have been tested. The subjects of the study are comprised of a total of 298 employees from eight large-sized hospitals. According to the findings of the study, NA has a positive relationship with job strain, functioning as a significant explanatory variable; whereas PA does not prove to act as a significant explanatory variable. By contrast, NA has no relationship with OCB, whereas PA has a highly positive relationship with it. Consequently, it can be assumed that affective disposition(PA/NA), on which a lot of studies have been recently conducted, plays an important role in the employee's attitude, behavior, and organizational performance. LMX also proves to be a significant explanatory variable in its relationship with job strain and OCB. High-quality in LMX reduces the employee's job strain while increasing OCB. The analysis of the moderating effects of POS in the relationship between affective disposition and LMX and job strain and OCB shows that POS has no moderating effects on job strain but significant moderating effects on OCB. The results imply that both LMX and POS should be managed together in order to administer OCB. This study has found that the higher the employee's positive affectivity and the lower the negative affectivity, the higher his/her contribution to the organization. These findings can be applied not only to the study of organizational behavior theoretically but to various practices, such as recruitment and selection, job rotation, and performance appraisal KCI Citation Count: 33